Reasons for medical rescue team interventions in the northwest part of masovian voivodeship - Zbigniew Białczak; Robert Gałązkowski; Patryk Rzońca; Adam Gorgol (Kazimierz Wielki University, 2018)
Introduction: Civilisation development and huge technological progress influence the life and functioning of every human being. They facilitate functioning in the modern world but are also associated with increased incidence of trauma and morbidity, which are a challenge for modern health care systems. One of the main elements of health care is Emergency Medical Services System, whose aim is to save people who are in the state of sudden health hazard. Aim: The aim of this paper was to analyse the reasons for medical rescue team interventions in the northwest part of Masovian voivodeship within the period of four years (2013-2016). Materials and method: The analysis showed that the most common reason for medical rescue team intervention in the studied region and time period was cardiovascular diseases. Results: Men and people aged 75-89 were the main beneficiaries of medical services provided by medical rescue teams. Cardiovascular diseases were more often diagnosed in women and people aged 75-89, while injuries were mainly diagnosed in men and people aged 45-59. Conclusion: The gender and age of the patient, year, day of the week, the place of the call, team type and the urgency code of the call were important factors influencing the reasons for the intervention of MRTs in the analysed region and period.